The enigmas of Sor Juana as devices of understanding - Ortiz-Díaz, Jesús Ernesto (2013)
Two years after the storm raised by the Carta Atenagórica (Letter Worthy of Athena) and, precisely two years before her death, Sor Juana sent to an Academy of Portuguese nuns (A Casa do Prazer) —assiduous readers not only of religious matters— a set of 20 riddles that have received little attention from the critics of her work. The brevity of these writings and their hermetic nature —taking into account the fact that the author has not given them a ultimate solution— have postponed being given the importance they deserve, for they might be the last finished work —conceived as a unit in itself— of the New-Spanish writer. What importance does this score of writings have, written by a nun to the amusement of other nuns? What significance do they acquireby being one of her last written works after having complied with the silence imposed on it? Are they an atypical curiosity, a feature that is out of place in the average physiognomy of her production? In her Enigmas offered to the Casa do Prazer we affirm that Sor Juana creates a trick of literary nature which, in the context of monastic rules, enables the exercise of free will from the public silencing to which she was subjected. The election of such device is extremely important because it makes use of a popular genre —the riddle or onundrum— associated with domestic and daily life —under the woman’s control— in order toarticulate and debate on grounds of what was unspeakable to nuns and women: theology and the other sciences.